Additions of new species and records to the Tanaidomorpha (Crustacea: Tanaidacea) of Taiwan - Tzeng, You-Wei; Hsueh, Pan-Wen (Zootaxa, 2015)
This study reports two new species and one new species record of tanaidomorphan tanaidaceans from Taiwan. The leptocheliid Leptochelia taitungensis sp. nov. can be separated from the most similar species, Leptochelia tarda, in the Leptochelia dubia/savignyi group by having long distal spines on the maxilliped endites and the male having two-articled uropod exopods. The tanaidid Zeuxo shitipingensis sp. nov. can be distinguished from Z. normani in the Zeuxo normani species-complex by having a triangular left mandible lacinia mobilis, only one seta on the pleopod endopod inner margin, and the uropod endopod with five to six articles in most adult specimens. Morphological comparisons between Leptochelia taitungensis sp. nov. and its congeners within the dubia/savignyi group, as well as between Zeuxo shitipingensis sp. nov. and its congeners, are tabulated.